District Fiscal Policy and Student Achievement - Gary G. Huang; Binbing Yu (Arizona State University, 2002)
School restructuring raises questions about the role of school districts in improving student learning. Centralization by state governments and decentralization to individual schools as proposed in systemic reform leave districts' role unsettled. Empirical research on the district role in the context of ongoing reform is inadequate. This analysis of combined data from the NAEP and the Common Core of Data (CCD) was intended to address the issue. We analyzed 1990, 1992, and 1996 NAEP 8th grade mathematics national assessment data in combination with CCD data of corresponding years to examine the extent to which student achievement was related to districts' control over instructional expenditure, adjusting for relevant key factors at both district and student levels. Upon sample modification, we used hierarchical linear modeling (HLM) to estimate the relationships of student achievement to two district fiscal policy indictors, current expenditure per pupil (CEPP) and districts' discretionary rates for instructional expenditure (DDR). Net of relevant district factors, DDR was found unrelated to districts' average 8th grade math performance. The null effect was consistent in the analysis of the combined NAEP-CCD data for 1990, 1992, and 1996. In contrast, CEPP was found related to higher math performance in a modest yet fairly consistent way. Future research may be productive to separately study individual states and integrate the findings onto the national level.